Legal Measures for The Prevention of Marine Pollution from Abandoned Fishing Gears in Thai Waters - Asasappakit, Sakunphun (Law for Development Graduate Journal, 2024)
Commercial fishing in Thai waters surpasses the scale of artisanal fishing, involving numerous fishing vessels and gear. Consequently, the risk of these fishing implements suffering damage, getting lost, or being discarded into the sea exists, whether through intentional actions or inadvertent occurrences by fishermen. Regrettably, the Abandoned, lost, or otherwise discarded fishing gear (ALDFG) at sea inflicts severe harm upon coral reefs and other marine ecosystems, significantly contributing to the issue of marine pollution. This persistent problem is rooted in the absence of proper marking on fishing gear. Locating and recovering lost or discarded fishing gear at sea poses considerable challenges, further exacerbated by the government’s inability to establish ownership of such equipment. This includes ownership information, associations with fishing vessels, and vessel registration details. Consequently, determining the owner of fishing gear lost or discarded becomes a daunting task, impeding the enforcement of existing laws and perpetuating the risk of marine pollution. The purpose of this independent study is to examine legal measures to prevent marine pollution caused by fishing gear that is abandoned, lost, or discarded into the sea without any markings on the fishing gear. This study contributes to the analysis of measures to identify the ownership of fishing gear to establishing mandatory marking of fishing gear as a regulatory measure and appropriate government organizations in regulating the problem. This comprehensive study encompasses an exploration of foundational principles within the domain of environmental law, encompassing both domestic legislation in Thailand and international law, even extending to non-binding international rules. Its overarching purpose is to discern and recommend appropriate regulatory measures to combat the issue of marine pollution stemming from the abandonment of fishing gear at sea, with a comparative evaluation of Thailand’s legal framework against international conventions and guidelines established by international organizations. Through the study, it has been discerned that Thailand’s existing legal provisions, while capable of penalizing individuals responsible for marine resource damage, lack the necessary mechanisms to establish ownership of fishing gear. This limitation obstructs the legal process to hold such offenders accountable, rendering the current legal framework insufficient in preventing marine pollution. In the absence of amendments addressing ownership verification of fishing gear, it is foreseeable that such issues will persist, perpetuating irreparable harm to Thailand’s marine resources. Consequently, Thailand must institute effective measures to address this issue. This involves the implementation of a comprehensive system for marking fishing gear used in commercial fishing within Thai waters. Drawing inspiration from the voluntary guidelines established by the Food and Agriculture Organization of the United Nations and pertinent Department of Fisheries directives, such a system should be designed for practical implementation. Additionally, it necessitates the delegation of oversight responsibilities to relevant organizations proficient in managing these concerns.